Optimum Investigation LED Bulbs Light as Photon Energy on Photovoltaic Panel Installed Inside Buildings - Mustofa Mustofa; Anjar Asmara; Yuli Asmi Rahman; Tutang Muhtar Kamaludin; Zuryati Djafar; Wahyu Hariyadi Piarah; Hariyanto Hariyanto (EPI International Journal of Engineering, 2021)
This study was conducted to obtain the angle of elevation of solar panels (PV) to harvest photon light energy sources from LED bulbs that are often used in residential homes or buildings. The PV tilt angles tested are 0, 15, 30 and 90º by placing a constant bulb in its position. The results of the observations show that a slope of 0º produces the highest PV electrical power, although it is not significant compared to the other 3 slope angles. The decrease in PV output power occurs when the slope angle increases. Optimum power of 16.93 Watt is obtained by using a Hannochs bulb at a power of 15 Watt with an angle of elevation of 0º. Furthermore, the power decreased to 16.33, 12.92, and 12.91 Watts at angles of 15, 30 and 90º, respectively. Further research is still needed by increasing the variation of bulb power above 15 Watts to validate the position of the PV panels on the walls of the building according to light source.